Pengeloaan Zakat dan Wakaf di Indonesia dalam UU No. 23 Tahun 2011 dan UU No. 41 Tahun 2004 - Khoirul Ma'arif (Journal Islamic Economic and Bussines Studies, 2022)
Zakat and Waqf are two very important institutions in the social and economic development of society in Indonesia. These two institutions are part of Islamic teachings that regulate the management of property and social obligations of Muslims. Although it has the same purpose, namely to help underprivileged people and promote the welfare of society, zakat and Waqf have differences in terms of collection, management, use, and legal protection. The purpose of this study was to determine and understand the difference between zakat and Waqf in Indonesia, which includes differences in terms of collection, management, use, legal protection, and recipient groups. This study uses the principles of Islamic law in the study of differences in zakat and Waqf in Indonesia. These principles are applied in every stage of research, from topic selection, sources assistance, literature review, sources selection, and data analysis, to report writing. These principles are used to ensure that the study is in accordance with Islamic teachings and does not contradict religious values. The method used in this study is the descriptive-comparative analysis method. This method is used to explain and analyze the difference between two or more variables, namely the difference between zakat and Waqf in Indonesia. The results concluded, zakat and Waqf are two institutions that are very important in the social and economic development of society in Indonesia. These two institutions are part of Islamic teachings that regulate the management of property and social obligations of Muslims. Although they have the same purpose, which is to help underprivileged people and promote the welfare of society, these two institutions have differences in terms of collection, management, use, and legal protection.